Default Inheritance in Modified Statements: Bias or Inference? - Strößner, Corina (Frontiers in Psychology, 2021)
It is a fact that human subjects rate sentences about typical properties such as `Ravens are black' as very likely to be true. In comparison, modified sentences like `Feathered ravens are black' receive lower ratings, especially if the modifier is atypical for the noun as in `Jungle ravens are black'. This is called the modifier effect. However, the likelihood of the unmodified statement influences the perceived likelihood of the modified statement: the higher the rated likelihood of the unmodified sentence, the higher the rated likelihood of the modified ones. That means the modifier effect does not fully block the default inheritance of typical properties from nouns to modified nouns. This paper discusses this inheritance effect. In particular, we ask whether it is the direct result of composing concepts from nouns, that is, a bias towards `black' when processing `raven'. We report a series of experiments in which we find no evidence for a direct inheritance from composition. This supports the view that default inheritance is rather an inference than a bias.